Onobrychis maassoumii (Fabaceae-Hedysareae), a new species from Iran - Kaveh, Akram; Amirahmadi, Atefe; Nafisi, Haniyeh; Kazempour-Osaloo, Shahrokh (Phytotaxa, 2019)
Onobrychis maassoumii Kaveh, Amirah. & Kaz. Osaloo sp. nov. is described and illustrated as a new species. It is restricted to Alborz mountain range in northeastern Tehran, Iran. Morphologically, this species is distinct from its closest relatives by greenish appearance, leaflets with upper glabrescent surface, calyx teeth 2–2.3 times as long as tube and petal wings ciliate. Also, molecular evidence reinforced this species as a distinct taxon. The distribution map and an illustration of the new species are also provided.